ASSOCIATION STUDIES BETWEEN POLYMORPHIC MARKERS TLR2 AND TLR9, PRE-TERM DELIVERY AND INTRAUTERINE INFECTIONS - O. .A. Gankovskaya (Медицинская иммунология)
During last years, a role of genetic factors in maturation of innate immunity functions was actively studied. It is known, that some SNP in TLR9 and TLR2 genes are known to be associated with development of infection in pregnancy. However, interrelations of various TLR-mediated anti-infectious mechanisms with genetic factors in pregnant women were poorly studied. The aim of present study was to evaluate associations between the following SNPs: Arg677Trp, Arg753Gln of TLR2 gene, A2848G SNP of TLR9 gene, and frequencies of pre-term birth complicated by infections in Russian population of Moscow City. SNPs Arg677Trp, Arg753Gln in TLR2 gene have been studied in a clinical material by means of PCR-RFLP analysis, using AciI restrictase. A2848G polymorphic marker in TLR9 gene was assessed by real-time PCR, employing TaqMan probes. It has been shown, that Arg allele of Arg753Gln TLR2 gene was associated with urogenital infections. When studying A2848G polymorphism in TLR9 gene, the A Allele was associated with normal delivery, thus assuming the A2848G polymorphic marker as a protective one.